The Role Of BNPB In Nonstructural Mitigation Efforts Against The Threat Of Earthquakes In The Cianjur Cugenang Fault Area - Gustin Restu Pangestu; Berton Suar Pelita Panjaitan; Achmed Sukendro; Pujo Widodo; Herlina Juni Risma Saragih (CV. AFDIFAL MAJU BERKAH, 2024)
The 2022 earthquake in Cianjur Regency has claimed many lives, caused damage and large material losses. In addition, there are findings of new active faults in the Cugenang area that can potentially threaten the safety of the population. Therefore, it is necessary for the Government to reduce physical and material losses and reduce the number of casualties if a similar incident occurs again. BNPB is the leading sector in disaster management in Indonesia, one of which is disaster risk reduction efforts. This study aimed to analyze the role of BNPB in the efforts of nonstructural mitigation activities in the Cugenang Fault area of Cianjur Regency. The research method used was qualitative with an exploratory design. The data in this study were obtained from interviews, documentation, and observation in Cugenang District. The results of this study showed that BNPB's role in nonstructural mitigation efforts was carried out through activities: Policy Recommendation for post-disaster spatial plan of Cianjur 2022, Dissemination of information about the risk of natural disasters in Cugenang, Preparation of disaster risk assessment 2023. Conclusion The Cugenang Fault is an active fault that is prone to earthquake threats. Therefore, the government is obliged to protect the community from the threat of earthquakes through nonstructural mitigation activities. The research suggestion is for the local government to make a RTRW policy to protect the community from earthquakes through nonstructural mitigation activities.